Uji Keefektifan Formulasi Bacillus subtilis untuk Mengendalikan Penyakit Busuk Batang Fusarium pada Tanaman Jagung In Vivo - Suriani, Suriani; Djaenuddin, Nurasiah; Muis, Amran (Jurnal Penelitian Pertanian Tanaman Pangan, 2018)
Stalk rot diseases in corn caused by the fungus Fusarium verticilloides is one of the problems of increasing maize productivity. This pathogen can be transmitted through seed and soil. The method of control through seedtreatment with biological control is one of an effective control method of the soilborne pathogen. This research aimed to study the effectiveness B. subtilis formulation in controlling stalk rot disease.  The experiment was conducted in the plant Pathology Laboratory and in the greenhouse of Indonesia Cereals Research Institute (ICERI) from April 2017 to January 2018. The treatment used 8 formulation of B. subtilis of ICERI collection, synthetic fungicide and positive control. In vitro test was inhibition 8 formulation of B. subtilis to F. verticilloides growth by dual culture method. While activity in the green house is to test of effectiviness 8 formulation of B. subtilis in controlling the stalk rot. Seedtreatment of B. subtilis formulation TLB1, BS-BJ6, BS-M3, BS-TM4, BS-BNt4, BS-BNt5, BS-BNt6, BS-BNt8 and two controls (K1 with the use of synthetic fungicides and K2 with steril destiled water). Data collected were percentage inhibition of the growth of F. verticilloides miselia, disease incidence, and plant height. The results showed that formulation of B. subtilis BNt4 performed the best to inhibited growh of  the F. verticilloides in vitro test. Application of  B. subtilis  formulations BNt4 and TM3 by means of seed treatment can suppress stalk rot attack. The all of B. subtilis  formulations can stimulate plant growth.